Answer:
36
Explanation:
In the above question, we were told that
Given a * b = ba−ba+ab
We are to find (2*3)×(3*2)
Step 1
We simplify each bracket first
a * b = ba−ba+ab
2*3, a = 2, b = 3
2*3 = 3×2 - 3×2 + 2×3
= 6 - 6 + 6
= 6
a * b = ba−ba+ab
3*2, a = 3, b = 2
3*2 = 2×3 - 2×3 + 3×2
= 6 - 6 + 6
= 6
Step 2
(2*3)×(3*2)
= 6 × 6
Let us note that * = × as well. So we would apply the above rule also for our final calculation
a * b = ba−ba+ab
a = 6, b = 6
6 ×6 - 6×6 + 6×6
= 36 - 36 + 36
= 36
The answer is 36
The answer is 36